Property Taxation, Bounded Rationality and House Prices - Mikael Elinder; Lovisa Persson (Research Institute of Industrial Economics (IFN), 2014)
In 2008, the Swedish property tax was reformed and a cap on yearly tax liabilities was introduced. A large fraction of owner occupied houses was subject to a substantial decrease in the tax. When the reform was announced, most analysts projected - in line with tax capitalization theory - that the tax decrease would lead to significant increases in house prices. We estimate price responses and capitalization degrees, using various DID strategies, in which the price dynamics of houses that were subject to a generous tax reduction are compared to the price dynamics of houses with a more modest reduction. Our results are largely inconsistent with capitalization theory. For the majority of properties, we find no evidence that the tax cut led to increases inhouse prices. However, we find evidence of partial capitalization in sub-markets with highly valued properties, highly educated citizens and were it is especially difficult to increase supply. We argue that theories of bounded rationality can help explain why house buyers may fail to take a tax decrease into account in the valuation of houses.
Keywords: D01; D03; D04; D12; H22; H24; R21; R38; 330; Announcement effects; Capitalization; Financial literacy; Housing market; Inattention; Saliency